MACHINE LEARNING ALGORITHMS - A REVIEW - Tanuja Verma (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
In this paper, various machine learning algorithms have been talk about. These algorithms are used for various purposes like data mining, image processing, predictive analytics, etc. The main advantage of using machine learning is that, once an algorithm grasp what to do with data, it can do its work automatically